Trends of vital signs with gestational age in normal pregnancies: a systematic review protocol - Loerup, Lise; Pullon, Rebecca M; Birks, Jacqueline; Fleming, Susannah; Mackillop, Lucy H; Watkinson, Peter J (BMJ open, 2016)
IntroductionVital signs (blood pressure, heart rate, temperature, oxygen saturation and respiratory rate) are thought to undergo changes during and immediately after pregnancy. However, these physiological changes are not taken into account in the normal ranges, which themselves are not evidence-based, used in routine and acute care monitoring. We aim to synthesise the existing evidence base for changes in vital signs during pregnancy, in order to derive new centile charts for each stage of pregnancy and the immediate postpartum period.Methods and analysisWe will search the MEDLINE, EMBASE and CINAHL databases from their inception to April 2015 for vital signs from pregnant, intrapartum or postpartum women who were recruited as ‘healthy’. Assessment of bias will be conducted using a predefined set of independently agreed methodological criteria, which assigns an overall quality score to each study. We will record whether the vital sign measurements were made with measurement devices validated for use in pregnancy and in a standard posture. We will use regression methods to construct centile charts of vital signs across pregnancy and the immediate postpartum period for each vital sign. We will compare existing reference ranges to those derived from our centile charts.DisseminationThe systematic review will be published in a peer-reviewed journal and disseminated electronically and in print.PROSPERO referenceCRD42014009673.